Role of analogies with classical physics in introductory quantum physics teaching - Luiza Vilarta Rodriguez; Jan T. van der Veen; Ton de Jong (Physical Review Physics Education Research)
In this study, we explore the use of analogies with classical physics in introductory quantum physics (QP) teaching. This work is part of a larger project in which a learning sequence covering three introductory QP topics was designed, tested, and evaluated in collaboration with high school teachers and physics education researchers. Based on the theoretical foundations of guided inquiry-based learning and collaborative learning, three lessons covering the topics of photoelectric effect, wave-particle duality, and tunneling were developed. For each lesson, a digital inquiry learning space (ILS) was created which implemented a digital laboratory for performing experiments with specific interactive assignments and multimedia material. For this study, each ILS was adapted into two distinct versions, to be applied with students in two experimental conditions: one in which analogies with classical physics were present in the lessons, and one in which such analogies were avoided. Six classes of Dutch upper-secondary students (n=89) were assigned to one of the conditions and followed the respective version of the learning sequence during a period of approximately 6 weeks. Students’ answers to ILS activities were logged and used for a qualitative analysis. Once the learning sequence was finished, students took a post-test covering all three QP topics and scores were compared between the analogy and no analogy conditions. After correcting for students’ overall performance in physics, we found that students in the no analogy condition scored significantly higher on the post-test than the analogy condition for two out of the three QP topics (wave-particle duality and tunneling). An accompanying qualitative analysis suggests that the use of analogies with classical physics might hinder QP learning, as some students manifested difficulties in grasping the limitations of the classical analogies that were used in the materials.